Recovery of Nickel from spent hydrogenation catalyst using Chelating resin - Dzulkefly, K.; Haron, M.J.; Lim, Wen Huei; Woon, Chin Chan (Japan Oil Chemists’ Society, 2002)
Spent catalyst samples from hydrogenation of palm and palm kernel oils were subjected to soxhlet extraction to remove oil residue, digestion with concentrated sulfuric acid and nickel extraction using chelating ion exchange resin. The results showed that the spent catalysts contained oil residue (42.2-54.0%), nickel (11.32-15.63%), Mg (1.65-2.51%), Ca (3.84-5.68%). Other metals, Fe, K, Na, K, Al, Zn, Cu, Cr and Mn are minor components (<0.1%). The Amberlite IRC-718 resin has extracted more than 90% Ni in the spent catalysts (as nickel nitrate) with purity of higher than 90% with regards to the amount of Mg and Ca in the sample. The Amberlite resin showed the highest sorption capacity for Ni(II) (56.8 mg/g) at pH 5.